2021
DOI: 10.1097/md.0000000000026245
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Kanglaite injection combined with chemotherapy for women breast cancer

Abstract: Background: Breast cancer was the second cause of cancer death and approximately accounted for 30% of all newly diagnosed cancer in American women. Adjuvant chemotherapy is the preferred treatment approach for breast patients. Kanglaite injection (KI) was commonly used as adjuvant chemotherapy combined with chemotherapy for women breast cancer which could increase chemotherapy efficacy and alleviate chemotherapy drugs induced adverse events, however, the efficacy and safety for KI combined western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[34][35][36][37] Clinical application of KLTi in the treatment of BC has revealed that patients who receive combined chemotherapy demonstrated improved levels of T cell subsets, quality of life, and enhanced immune function. 10,11 However, there are currently no clinical data on KLTi in TNBC patients. A preclinical study found that KLTi can inhibit tumor growth in a TNBC mouse model, exerting an anti-TNBC effect by interfering with the miR-205/S1PR1 axis, regulating sphingomyelin metabolism, and partially affecting the downstream STAT3/MAPK/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] Clinical application of KLTi in the treatment of BC has revealed that patients who receive combined chemotherapy demonstrated improved levels of T cell subsets, quality of life, and enhanced immune function. 10,11 However, there are currently no clinical data on KLTi in TNBC patients. A preclinical study found that KLTi can inhibit tumor growth in a TNBC mouse model, exerting an anti-TNBC effect by interfering with the miR-205/S1PR1 axis, regulating sphingomyelin metabolism, and partially affecting the downstream STAT3/MAPK/AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…KLTi has been used clinically to treat numerous cancers, including non-small cell cancer, 7 gastric cancer, 8 pancreatic cancer, 9 and BC. 10 , 11 Preclinical studies have identified that KLTi exerts antitumor effects by regulating the PI3K/AKT/mTOR signaling pathway and the miR-205/S1PR1 axis. 12 , 13 However, the exact anti-tumor mechanisms are still not fully understood and deserve further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…With the research on the biology of breast cancer, in addition to the early diagnosis of breast cancer, improving the cure rate of breast cancer and selecting more effective drugs for treatment are of great significance to medical research. Chemotherapy has been used as one of the main tools in the treatment of cancer (2021) ( Cheng et al, 2021 ). There are many drugs available for the treatment, but most of these drugs are quite toxic, which may shorten the life span of cancer patients.…”
Section: Introductionmentioning
confidence: 99%